An Analysis of the Grammatical Cohesion in the Descriptive Text Written by the Fourth Semester Students of Universitas Mahasaraswati Denpasar - Amut, Maria Yustika; Ardiantari, Ida Ayu Putri Gita (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The title of this research was an analysis of the grammatical cohesion used in the descriptive text written by the fourth semester students of Universitas Mahasaraswati Denpasar. The objectives of this research are to find out the types of grammatical cohesion and how are the used of grammatical cohesion in the descriptive text written by fourth semester students of Universitas Mahasaraswati Denpasar. To analyze the data, the researcher used the theory of cohesion proposed by Halliday and Hasan (1976). The method that the researcher use in this study was the qualitative and quantitative method. As a result, there are two types of grammatical cohesion found in the descriptive text written by fourth semester students, they are reference, and conjunction. There is no ellipsis and substitution type found in the descriptive text. The most dominant type in the text found was the conjunction. The used of conjunction are the additive conjunction with a total use of 47%, the adversative conjunction with a total use of 16%, the temporal conjunction with a total use of 6% and causal conjunction with a total use of 4%.